Critical evaluation of pathogenic factors of primary biliary cirrhosis - A. F. Sheptulina; M. V. Mayevskaya; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2013)
The aim of review. Primary biliary cirrhosis (PBC) is related to the group of autoimmune cholestasisassociated liver diseases. In the last years prevalence of PBC increased considerably, especially – in Northern European countries. Despite of sufficient progress in studying of main pathophysiological mechanisms of PBC, etiology of disease remains obscure. There was a task to fill these gaps to some extent.Key points. Etiological factors increasing risk of PBC development include genetic factors, immunologic disorders, and environmental features. Thus the contribution of each of the mentioned groups of factors, at least, partly is determined by demographic, ethnic and geographical features.Conclusion. Detection of risk factors and the possible PBC causes allows to develop additional treatment approaches, and define new PBC markers, increase rate of early stage diagnostics.